1994
DOI: 10.1002/j.2050-0416.1994.tb00811.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Barley Endosperms During Early Stages of Germination*

Abstract: Kernels of 4 barley cultivars were germinated at 18°C and samples were removed for analysis at short time intervals for the first 30 h and at longer intervals during the ensuing 90 h. o-Amyiase,(1 ■;!)(! 4)-/J-glucanose and (1 -> 3) 0-glucanase activities were measured in each sample. Analysis of kernel sections stained with Calcofluor showed that hydrolysis of /j-glucan in the crushed cell layer commenced 6-9 h after the initiation of germination. Hydrolysis proceeded from the ventral adge to the dorsal edge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 2 publications
1
14
0
Order By: Relevance
“…They break down starch and storage proteins into simple molecules that nourish the growing embryo (Fincher 1989). Since starch and storage proteins are enclosed in the walls of the dead endosperm cells, these cell walls have to be dismantled to allow access of the hydrolytic enzymes to the internal reserves (Brown and Morris 1890;Gibbons 1980;Fincher 1989;MacGregor et al 1994;Brennan et al 1997;Briggs 1998). Breakdown of endosperm cell walls mainly involves degradation of b-glucans, which are the major constituent of the walls ([70%;Briggs 1998;Jin et al 2004).…”
Section: B-glucan Breakdown During Maltingmentioning
confidence: 98%
See 1 more Smart Citation
“…They break down starch and storage proteins into simple molecules that nourish the growing embryo (Fincher 1989). Since starch and storage proteins are enclosed in the walls of the dead endosperm cells, these cell walls have to be dismantled to allow access of the hydrolytic enzymes to the internal reserves (Brown and Morris 1890;Gibbons 1980;Fincher 1989;MacGregor et al 1994;Brennan et al 1997;Briggs 1998). Breakdown of endosperm cell walls mainly involves degradation of b-glucans, which are the major constituent of the walls ([70%;Briggs 1998;Jin et al 2004).…”
Section: B-glucan Breakdown During Maltingmentioning
confidence: 98%
“…1. Germination on moist paper can have a different progression (Briggs and MacDonald 1983;MacGregor et al 1994), possibly because of uneven exposition to water and oxygen.…”
Section: B-glucan Breakdown During Maltingmentioning
confidence: 99%
“…Germination is used as a tool to produce new, healthy, and tasty food ingredients from oats. It is predominantly synthesized in the aleurone and scutellum of germinated barley and secreted into the endosperm cells (MacGregor et al 1994) and subsequently degrades the β-glucan. However, the content and molecular weight of β-glucans are reduced during germination; the decrease in the molecular weight is slow initially but increases with an increase in germination temperature and duration (Wilhelmson et al 2001).…”
Section: Agronomic Practicesmentioning
confidence: 99%
“…A decrease in the level and molecular weight of β-glucan is due to hydrolysis of β-glucans by endogenous β-glucanase. It is predominantly synthesized in the aleurone and scutellum of germinated barley and secreted into the endosperm cells (MacGregor et al 1994) and subsequently degrades the β-glucan. However, little research has been reported on the relationship between seed and β-glucanase activity and the genetic and environmental variation of changes in β-glucan content and β-glucanase activity during germination.…”
Section: Agronomic Practicesmentioning
confidence: 99%
“…In order to achieve good malting quality, extensive endosperm breakdown, or modification, must accompany the germination phase of malting, with cell walls and protein being degraded and the starch granules exposed during the process. Therefore, hot water extract (HWE) of the resultant malt should yield a high of level of fermentable sugars from readily gelatinised starch granules that are depolymerised by malt amylases (MacGregor et al, 1994;Taylor, 1988, 1990;Swanston et al, 1995).…”
Section: Introductionmentioning
confidence: 99%